2021
DOI: 10.3389/fncel.2021.755955
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Role of Astrocytes in Ischemic Stroke

Abstract: Ischemic stroke refers to the disorder of blood supply of local brain tissue caused by various reasons. It has high morbidity and mortality worldwide. Astrocytes are the most abundant glial cells in the central nervous system (CNS). They are responsible for the homeostasis, nutrition, and protection of the CNS and play an essential role in many nervous system diseases’ physiological and pathological processes. After stroke injury, astrocytes are activated and play a protective role through the heterogeneous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 255 publications
(240 reference statements)
1
56
0
Order By: Relevance
“…The TRPV1 expression in the CNS has been investigated in numerous previous studies using different techniques; however, the available information concerning its cellular localization and regional distribution is still contradictory [ 48 , 49 , 71 , 72 , 73 , 74 , 75 , 76 ]. On the other hand, there is consensus regarding the involvement of TRPV1 in functions that, on the base of its multimodal activation, differ depending on the neuronal system/neuropathological condition considered [ 50 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRPV1 expression in the CNS has been investigated in numerous previous studies using different techniques; however, the available information concerning its cellular localization and regional distribution is still contradictory [ 48 , 49 , 71 , 72 , 73 , 74 , 75 , 76 ]. On the other hand, there is consensus regarding the involvement of TRPV1 in functions that, on the base of its multimodal activation, differ depending on the neuronal system/neuropathological condition considered [ 50 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, though with a time longer than that of our BCCAO/R model, it has been shown that the inflammatory milieu generated by 2.5 h of ischemic brain injury stimulated a strong astroglial response. This response was featured by cell hypertrophy and hyperplasia [ 77 , 80 ], and it was suggested that it may lead to an increased expression of GFAP, partly because the number of GFAP-positive astrocytes increases [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, astrocytes are activated under P2Y1 stimulation for dual roles with astrocyte-mediated excitatory amino acid transporter (EAAT) disorder and damage to aquaporin4, leading to glutamate excitatory cytotoxicity, cerebral blood flow disorder, and cerebral edema. Inflammatory factors also inhibit the proliferation and differentiation of cells of the OL lineage, resulting in demyelination and worsening prognosis [ 88 , 89 ].…”
Section: Mechanism Of Rna M6a-modified Glial Cells In the Occurrence ...mentioning
confidence: 99%
“…In the malignant secondary process of cerebral ischemic injury, astrocytes perform different functions at different stages, which are affected by many factors and mechanisms. Astrocytes activated by ischemic injury become reactive astrocytes, and under the influence of oxidative stress, inflammation, apoptosis, and other mechanisms caused by cerebral ischemic injury, they play a role in alleviating oxidative stress, releasing neurotrophic factors, producing excitatory toxicity, triggering inflammation, and glial scar formation ( 108 ). Astrocyte autophagy is one of the important regulatory mechanisms that plays an important role in the crosstalk between autophagy and other mechanisms.…”
Section: Crosstalk Between Astrocyte Autophagy and Other Mechanisms I...mentioning
confidence: 99%